Implementation of Social Rehabilitation Assistance for Children in Conflict with the Law at the Abiseka Center, Technical Implementation Unit, Ministry of Social Affairs of the Republic of Indonesia 2024 - Rafiq, Muhammad; Riky Novarizal (Sisi Lain Realita, 2024)
One of the social problems that occurs every year is deviant behavior in children. This requires professional social workers on an ongoing and competent basis to overcome this problem. The government established the Abiseka Center as a technical implementing unit in an effort to handle children in conflict with the law. This study aims to determine the implementation of social rehabilitation assistance for children in conflict with the law at the Abiseka Center in 2024 and the obstacles in its implementation. This study uses a qualitative method with a descriptive approach and data collection techniques through observation, interviews, and documentation. The results of this study indicate that the flow of implementing social rehabilitation assistance begins with the intake and engagement stages, assessment, intervention planning, implementation, monitoring and evaluation, termination, and supervision. Meanwhile, the obstacles that occur are still minimal professional staff with a social welfare background and inadequate infrastructure.